SEA-Teacher Students' Perspective: Challenges Teaching English Overseas in the Philippines - Christie Urai Musa; Ariyanti Ariyanti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
This qualitative research helps explore and understand the meaning of human action by describing the essential characteristics of a social or human experience (Astalin, 2013). This research aims to investigate SEA-Teacher students' challenges in teaching English overseas in the Philippines in terms of difficulties, motivations, and knowledge during and after teaching English overseas. A semi-structured in-depth interview was conducted and applied to those four SEA-Teacher students to find out the challenges in teaching English overseas according to 7th batch of SEA-Teacher students in the Philippines. Those students had experienced teaching English subjects in other countries in the Philippines by joining the SEA-Teacher program, one of the Southeast Asian Ministers of Education (SEAMEO) programs and located in Bangkok, Thailand. Flow Qualitative Analysis by Miles, Huberman, & Saldana (2014) analyzes the data. The interview result showed that teaching process and teaching preparation were the most challenging in teaching English in other countries. Teaching preparation was challenging to work on the Philippines' lesson plan because of curriculum differences. They also found that they were challenging in their teaching process where they were hard to manage the classroom during their teaching class because of the students' attitude when they were not listening to the teacher's instruction. Their difficulties in teaching preparation and Process came from themselves where they did not have the confidence and knowledge to adapt to other countries full of different cultures.